Recent Advances in a Polydopamine-Mediated Antimicrobial Adhesion System - Singh, Indu; Dhawan, Gagan; Gupta, Seema; Kumar, Pradeep (Frontiers in Microbiology, 2021)
The drug resistance developed by bacteria during antibiotic treatment has been a call to action for researchers and scientists across the globe as bacteria and fungi develop ever increasing resistance to current drugs. Innovative antimicrobial/antibacterial materials and coatings to combat such infections has become a priority as many infections are caused by indwelling implants (e.g. catheters) as well as improving post-surgical function and outcomes. Pathogenic microorganisms which can exist either in planktonic form or as biofilms in water carrying pipelines are one of the sources responsible for causing water-borne infections. To combat this, researchers have developed nano-textured surfaces with bactericidal properties mirroring the topographical features of some natural antibacterial materials. Protein-based adhesives, secreted by marine mussels, contain a catecholic amino acid, 3,4-dihydroxyphenylalanine (DOPA), which, in the presence of lysine amino acid, empowers with the ability to anchor them to various surfaces in both wet and saline habitats. Inspired by these features, a novel coating material derived from a catechol derivative, dopamine, known as polydopamine (PDA) has been designed and developed with the ability to adhere to almost all kinds of substrates. Looking at the immense potential of PDA, this review article offers an overview of the recent growth in the field of PDA and its derivatives, especially focussing the promising applications as antibacterial nano-coatings and discussing various antimicrobial mechanisms including reactive oxygen species-mediated antimicrobial properties.